TAHLILAN’S REPERTOIRE IN SEBUAH CERITA TENTANG BID’AH DI DUSUN KAMI - Safana, Iftinan Rose Putri (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2025)
This research aimed to examine these short stories in order to dissect the themes, characters and plot to reveal the tahlilan repertoire. To achieve this goal, this research used Wolfgang Iser's Aesthetic Response theory. This research was qualitative in nature, the primary data came from the NUonline page and the secondary one in the form related previous texts. The data obtained was analyzed through several stages, namely identification, classification and interpretation. This study identified two key repertoires, namely the repertoire of religious norm, which described the concept of heresy and it's legal basis, and the repertoire of social norm, which explained the negative and positive perspective of tahlilan from two religious groups. Among these, the repertoire of religious norm was the most dominant, as it served as the foundation for the conflicting perspectives in the narrative. This research highlighted how different groups' interpretation of tahlilan based on religious arguments and social traditions, shaping the broader discourse on religious practices in society.